1987
DOI: 10.1111/j.1469-8137.1987.tb02932.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIFFERENTIATION IN TEMPERATURE‐ENFORCED SEED DORMANCY AMONG GOLF COURSE POPULATIONS OF POA ANNUA L.

Abstract: SUMMARYSeed germinability at high temperature (25 °C) was found to differ among golf course populations oiPoa annua L. located along a gradient of different intensities of turf irrigation and mowing practices. A seed germination index was calculated to express the effect of temperature on seed germination. The seed germination indices of the less managed populations from the golf roughs were uniformly low and less than 30 %, with a mean index of 5 %. Conversely, the germination indices of the golf green popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…It shows a pattern of primary dormancy that is lost through afterripening much like B. tectorum (Corbineau et al 1992). Strong genetic control for seed dormancy traits has been demonstrated in many wild species, including annual dicot weeds (e.g., Garbutt and Witcombe 1986 for Sinapis arvensis; Harper and McNaughton 1960; Lane and Lawrence 1995 for species of Papaver) and other sel®ng annual grasses (e.g., Wu et al 1987 for Poa annua). Naylor and Jana (1976) studied population genetics of seed dormancy in the primarily sel®ng annual grass Avena fatua.…”
Section: Discussionmentioning
confidence: 98%
“…It shows a pattern of primary dormancy that is lost through afterripening much like B. tectorum (Corbineau et al 1992). Strong genetic control for seed dormancy traits has been demonstrated in many wild species, including annual dicot weeds (e.g., Garbutt and Witcombe 1986 for Sinapis arvensis; Harper and McNaughton 1960; Lane and Lawrence 1995 for species of Papaver) and other sel®ng annual grasses (e.g., Wu et al 1987 for Poa annua). Naylor and Jana (1976) studied population genetics of seed dormancy in the primarily sel®ng annual grass Avena fatua.…”
Section: Discussionmentioning
confidence: 98%
“…This hypothesis is partially substantiated by Callahan and McDonald (1992), who reported that ABG germinated mostly between mid‐to‐late November and early January in Tennessee. Previous studies have shown that biotypes of ABG growing on greens, fairways, and roughs have different requirements for germination (Lush, 1989; Wu et al, 1987; Wu and Harivandi, 1993). While ABG seedling emergence was monitored in mostly nonirrigated roughs, it is unknown if similar emergence patterns occur on greens and fairways in Maryland.…”
Section: Discussionmentioning
confidence: 99%
“…However, germination differences among populations could well reflect inbreeding effects, and germination differences among individuals have important fitness consequences. Population differences in seed germination percentages and populations' responses to environmental conditions have been documented for many species (e.g., Farmer et al 1986;Wu et al 1987;Meyer et al 1989), but to consider the possible effects of fragmentation-caused reduced genetic variation, these germination differences must be correlated with population size and isolation. To my knowledge, no studies make this link.…”
Section: Mengesmentioning
confidence: 99%